Nanomedicine strategies for central nervous system (CNS) diseases - Nagri, Shreya; Rice, Olivia; Chen, Yupeng (Frontiers in Biomaterials Science, 2023)
The blood-brain barrier (BBB) is a crucial part of brain anatomy as it is a specialized, protective barrier that ensures proper nutrient transport to the brain, ultimately leading to regulating proper brain function. However, it presents a major challenge in delivering pharmaceuticals to treat central nervous system (CNS) diseases due to this selectivity. A variety of different vehicles have been designed to deliver drugs across this barrier to treat neurodegenerative diseases, greatly impacting the patient's quality of life. The two main types of vehicles used to cross the BBB are polymers and liposomes, which both encapsulate pharmaceuticals to allow them to transcytose the cells of the BBB. For Alzheimer's disease, Parkinson's disease, multiple sclerosis, and glioblastoma brain cancer, there are a variety of different nanoparticle treatments in development that increase the bioavailability and targeting ability of existing drugs or new drug targets to decrease symptoms of these diseases. Through these systems, nanomedicine offers a new way to target specific tissues, especially for the CNS, and treat diseases without the systemic toxicity that often comes with medications used currently.